Smart Solutions in Overcoming Family Conflict: The Wahdatul'ulum Approach - Nasution, Indah Widya Jaya Putri; Febrian, M Agil; Repi, Predi Ari; K, Putri Halimaini; Qomariah, Siti; Dahlan, Zaini (Academy of Education Journal, 2024)
Family conflict can occur at any time and is difficult to avoid due to a lack of understanding, communication, patience and acceptance of individual differences, resulting in conflict within the family. Therefore, the aim of this research is to find out how to solve family conflicts using the wahdatul 'ulum approach, which is a concept of scientific integration that unites religious knowledge and general science. This research uses qualitative research, data collection was carried out by interviews in one of the villages in Tamiang Hulu sub-district, Aceh Tamiang district. The results of this research are that family conflicts can be resolved using a transdisciplinary approach so as to create a holistic approach, which includes spiritual, emotional, rational aspects and Al-Qur'an counseling which is an effective solution in solving problems.